Worlds in Miniature : Contemplating Miniaturisation in Global Material Culture - Dixon, Charlotte; Davy, Jack (Book collections on Project MUSE., 2019)
Worlds in Miniature brings together researchers working across different regions, time periods and disciplines to explore the subject of miniaturisation as a material culture technique.